Extraction, purification and characterization of lysine from selected clinical isolate of Staphylococcus aureus and examination of its antibacterial activity against pathogenic bacterial species - Sheymaa S. Ismael; Entesar H. Ali; Iman I. Jabbar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Lysine is an α-amino acid that is a precursor to many proteins. Human body cannot synthesize lysine, but there are organisms can produce it. Lysine plays several roles in humans. Therefore, this study aimed to extract and purify lysine from different bacterial pathogens. 20 samples, that collected from wound and burn infections, were obtained from Baghdad hospitals. Bacteria isolated culturally on different media, then examined and identified via microscopic, biochemical tests, the API system, and the Vitek2 system. The predominant bacteria being 2 (33.34%) isolates of Staphylococcus aureus, and 2(33.34%) isolates of Pseudomonas aeruginosa, followed by 1 (16.67%) isolates of Escherichia coli and 1 (16.67%) isolates of Staphylococcus epidermidis. Then, S. aureus, P. aeruginosa and E. coli, that isolated from skin, were utilized to detection of lysine production using qualitative method (ninhydrin reagent) and quantitative analysis (ferric ninhydrin reagent). Only S. aureus was produced lysine at 6.78 mg/ml. To produce lysine, S. aureus was inoculated in Luria broth and produce lysine at 6.621 mg/ml and it reaching 8.45 mg/ml using HCL (1 N). Ion exchange chromatography was utilized for lysine purification, whereas its concentration reaching 9.434 mg/mL. The collected lysine solution was lyophilized and yielded 1.85 grams of a white-yellowish powder. For characterization of lysine, Fourier-transform infrared spectroscopy (FTIR) and Ultraviolet–visible spectroscopy (UV-vis) were utilized. UV-Vis revealed a maximum absorbance (λmax) of lysine at 300.77 nm. Zeta potential measurement of lysine was -46 mV, which determined using electrophoretic light scattering (ELS). Purified Lysine has a melting point at 271°C.